What makes a biostatistician? - Zapf, Antonia; Kieser, Meinhard (Statistics in medicine, 2019)
Biostatisticians play an important role in medical research. They are co-responsible for an appropriate and efficient study design, they are involved in monitoring the study conduct, they plan and perform the data analysis, and they are involved in interpreting and publishing the results. However, how are the biostatisticians prepared for their tasks and responsibilities? Graduate programs in biostatistics are being offered, but some practicing biostatisticians completed their studies in a mathematical or epidemiological program, or obtained their degree in subject-specific fields (such as medicine or biology). Therefore, the expertise and the competencies can vary widely between the individual biostatisticians, also depending on the application field. In this article, focusing on European and US practices, we discuss the required professional expertise for the main areas of applications in the medical field as well as the necessary soft skill competencies of a biostatistician.
First published: 07 October 2018
Gesehen am 15.02.2019